2007
DOI: 10.1902/jop.2007.060214
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Photodynamic Therapy on the Development of Ligature‐Induced Periodontitis in Rats

Abstract: PDT transiently reduced the periodontal tissue destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
68
0
18

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 60 publications
11
68
0
18
Order By: Relevance
“…The histomorphometric results of this study support these findings; although SRP and aPDT as isolated treatments also showed some effectiveness (mainly SRP), the best results were achieved with the combination of SRP and aPDT. The results corroborate animal [28,29] and human studies [30,31], which demonstrated that aPDT may be useful as an adjuvant to mechanical therapy in periodontitis treatment.…”
Section: Discussionsupporting
confidence: 86%
“…The histomorphometric results of this study support these findings; although SRP and aPDT as isolated treatments also showed some effectiveness (mainly SRP), the best results were achieved with the combination of SRP and aPDT. The results corroborate animal [28,29] and human studies [30,31], which demonstrated that aPDT may be useful as an adjuvant to mechanical therapy in periodontitis treatment.…”
Section: Discussionsupporting
confidence: 86%
“…The histomorphometric results of this study are in agreement with such statements, since although the SRP or aPDT as isolated treatments have shown some effectiveness (mainly SRP), the best results were achieved with the combination of mechanical removal of the biofilm by SRP + aPDT. Our results corroborate animal [33,34] and humans studies [35,36], which demonstrated that the aPDT may be useful as an adjuvant to mechanical therapy in periodontal disease treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies were developed using the concentration of 100 µg/mL of MB [33,34] or TB [38], and favorable results were obtained when using aPDT as an adjuvant to SRP for the treatment of Anexos | 96 periodontitis induced in rats. On the other hand, human clinical trials have used the MB in concentration of 10 mg/mL [35,39,50,51]; and some of these studies have found that there is no advantage in using aPDT as an adjuvant therapy for the treatment of periodontal disease [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Microbiological reduction was observed in vivo following photodynamic therapy in the treatment of peri-implantitis in dogs (91,92). Also, it was reported in an animal model that photodynamic therapy can reduce periodontal disease progression and periodontal tissue destruction in experimentally induced periodontal disease (93) Therefore, the potential effects of photodynamic therapy should be studied more extensively to establish the optimal conditions during clinical application. However, photodynamic therapy holds promise as a novel, non-invasive treatment method that might be beneficial when applied alone or in conjunction with conventional mechanical periodontal and peri-implant therapy.…”
Section: Other Usesmentioning
confidence: 99%